Impact of Bonus Compensation, Political Costs, and Opportunistic Behavior on Earnings Management in the Indonesian Insurance Industry (2019-2023) - Nugroho, Tatas Ridho; Miftakh, Eliza Silviana; Oktaviana, Mifta Ria; Mu’thoyyah, Izzatul (Formosa Journal of Multidisciplinary Research, 2024)
This study investigates the effects of bonus compensation, political costs, and opportunistic behavior on earnings management within the Indonesian insurance sector from 2019 to 2023. During this period, heightened regulatory scrutiny and the economic challenges posed by the COVID-19 pandemic intensified pressures on financial reporting. Using a quantitative approach, this study analyzes data from the financial statements of insurance companies listed on the Indonesia Stock Exchange, applying multiple regression analysis to examine the relationships between the variables. The findings reveal that political costs significantly increase earnings management practices, supporting Positive Accounting Theory by indicating that firms under regulatory pressure tend to smooth income to reduce scrutiny. In contrast, bonus compensation is negatively associated with earnings manipulation, aligning with Agency Theory by suggesting that well-structured incentives align managerial actions with shareholder interests, thereby reducing manipulation.